Reforma Agraria dan Aliansi Kelas Pekerja di Indonesia - Tolo, Emilianus Yakob Sese (Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
Land tenure system is a crucial factor for the development of the nation. As a developing country, Indonesia is still encountering serious problems related to unequal land tenure system, indicated by the continuing rise of the Gini index of the land ownership year by year. This has negative implications for productivity and livelihoods. Therefore, agrarian reform is an urgent need that must be executed immediately. The agrarian reform in Indonesia should be led and pioneered by the alliance of the working class: the industrial workers (laborers) and farmers. The author argues that the alliance of the working class will have an impact on realization of agrarian reform which could lead the nation to the better development. However, agrarian reform must also be supported by other sectors such as cooperatives and village industrialization. However, these sectors are necessary to put into practice sustainable economic democracy after implementing agrarian reform so as to escape from capitalism logic of capital accumulation.